Infection by Ehrlichia canis and Anaplasma sp. in dogs attended in veterinary clinics, Barranquilla, Atlántico (2017)
Determine the prevalence of infection by Ehrlichia canis and Anaplasma sp. and its correlation with epidemiological and laboratory aspects, in dogs treated in veterinary clinics in Barranquilla, Colombia. Materials and methods. Retrospective, descriptive cross-sectional study. The data was obtained between the months from January to August 2015. 184 dogs that clinically presented the infection with these agents were studied. Criteria for positivity were immunochromatography kit and blood smear, epidemiological and laboratory data. Results. Global prevalence was ascertained as 34% (63 dogs), 28% (52/184 dogs) for E. canis and 6% (11/184 dogs) to Anaplasma sp. Hemogram of dogs infected with both bacteria were hematocrit decreased, they also showed leukopenia and thrombocytopenia. Conclusions. Findings reported in this study show a high prevalence and endemicity of E. canis y Anaplasma sp. in Barranquilla when compared with other colombian regions. Hemogram findings showed to be relevant to diagnostic and prognostic of these infectious diseases.